2022
DOI: 10.1155/2022/2621969
|View full text |Cite
|
Sign up to set email alerts
|

Identification of VASH1 as a Potential Prognostic Biomarker of Lower-Grade Glioma by Quantitative Proteomics and Experimental Verification

Abstract: Background. VASH1 is a novel angiogenic regulatory factor, that participates in the process of carcinogenesis and the development of diverse tumors. Our study aimed to investigate the expression and prognostic value of the VASH1 in Lower-Grade Glioma (LGG), to explore its functional network in LGG and its effects on biological behaviors. Methods. LGG transcriptome data, somatic mutation profiles and clinical features analyzed in the present study were obtained from the TCGA, GTEx, CCLE, CGGA, UALCAN, and GEPIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Cell Proliferation Assays. Referring to previous studies' experimental methods [23][24][25], the BGC-823 cell line was used for subsequent analyses. To evaluate the proliferative capacity of GC cells after KYNU silencing, BGC-823 cells were transfected with KYNU-shRNA and NC-shRNA.…”
Section: Determination Of the Relationship Between Kynu-related Cells...mentioning
confidence: 99%
“…Cell Proliferation Assays. Referring to previous studies' experimental methods [23][24][25], the BGC-823 cell line was used for subsequent analyses. To evaluate the proliferative capacity of GC cells after KYNU silencing, BGC-823 cells were transfected with KYNU-shRNA and NC-shRNA.…”
Section: Determination Of the Relationship Between Kynu-related Cells...mentioning
confidence: 99%
“…In vitro and in vivo studies have shown that miR-320a can up-regulate cyclin-dependent kinase 2 by directly binding to the downstream target PBX3, thereby inhibiting the proliferation and growth of HCC cells [22]. Literature [23] has revealed that exosome and ubiquitination-related cyclic RNAcirc-DB is up-regulated in patients with HCC with high body fat. CIRC-DB promotes the growth of liver cancer cells and reduces DNA damage by inhibiting miR-34a and activating USP7/CY-Clina2 signaling pathway related to deubiquitination.…”
Section: Immunotherapy Reversalmentioning
confidence: 99%